Microwave-Assisted Syntheses of Vegetable Oil-Based Monomer: A Cleaner, Faster, and More Energy Efficient Route - Alarcon, Rafael T. [UNESP]; Gaglieri, Caroline [UNESP]; de Souza, Otávio A. [UNESP]; Rinaldo, Daniel [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2020)
Modification of vegetable oil into monomers and polymers is essential nowadays, considering petroleum depletion. The reaction of vegetable oils with maleic anhydride is widely known, and the final product can be obtained by a thermal conventional route, which requires 3 h for total reaction. The aim of this work was to provide a more efficient, faster, and cleaner alternative synthetic route assisted by microwave irradiation. A comprehensive experimental design indicated that it is possible to obtain higher anhydride incorporation onto vegetable oil structure with only 15 min of microwave irradiation, a reaction time 12 × less than the thermal conventional route, as well as 6 × less energy consumption. Furthermore, the higher performance was supported by the Mid-Infrared Spectroscopy (MIR), Nuclear Magnetic Resonance (1H-NMR), and UV–Vis analyses. The viscosity and colorimetric analyses were used to determine the aspect of modifications of final product. Thermogravimetry (TG) is fundamental to afford thermal stability and steps of mass loss, and Differential Scanning Calorimetry (DSC) provides information about melting point, which proves the incorporation of the anhydride.
Keywords: Central composite design; Green chemistry; Maleic anhydride; Microwave irradiation; Renewable material